Do Head-Mounted Augmented Reality Devices Affect Muscle Activity and Eye Strain of Utility Workers Who Do Procedural Work? Studies of Operators and Manhole Workers. (March 2022) - Marklin, Richard W.; Toll, Ashley M.; Bauman, Eric H.; Simmins, John J.; LaDisa, John F.; Cooper, Robert
Objective: The objective was to determine the effect of two head-mounted display (HMD) augmented reality (AR) devices on muscle activity and eye strain of electric utility workers. The AR devices were the Microsoft HoloLens and RealWear HMT-1. Background: The HoloLens is an optical see-through device. The HMT-1 has a small display that is mounted to the side of one eye of the user. Method: Twelve power plant operators and 13 manhole workers conducted their normal procedural tasks on-site in three conditions: HoloLens, HMT-1, and "No AR" (regular method). Duration of test trials ranged up to 30 s for operators and up to 10 min for manhole workers. Mean and peak values of surface electromyographic (sEMG) signals from eight neck muscles were measured. A small eye camera measured blink rate of the right eye. Results: In general, there were no differences in sEMG activity between the AR and "No AR" conditions for both groups of workers. For the manhole workers, the HoloLens blink rate was 8 to 11 blinks per min lower than the HMT-1 in two tasks and 6.5 fewer than "No AR" in one task. Subjective assessment of the two AR devices did not vary in general. Conclusion: The decrease in blink rate with the HoloLens may expose utility manhole workers to risk of eye strain or dry-eye syndrome. Application: HMD AR devices should be tested thoroughly with respect to risk of eye strain before deployment by manhole workers for long-duration procedural work.